2020
DOI: 10.1103/physrevd.101.026021
|View full text |Cite
|
Sign up to set email alerts
|

Chaos and complexity in quantum mechanics

Abstract: We propose a new diagnostic for quantum chaos. We show that time evolution of complexity for a particular type of target state can provide equivalent information about the classical Lyapunov exponent and scrambling time as out-of-time-order correlators. Moreover, for systems that can be switched from a regular to unstable (chaotic) regime by a tuning of the coupling constant of the interaction Hamiltonian, we find that the complexity defines a new time scale. We interpret this time scale as recording when the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
106
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 79 publications
5
106
0
Order By: Relevance
“…This approach was first applied to a concrete quantum field theory calculation in [57], where the authors adapted Nielsen's approach to evaluate the complexity of the vacuum state of a free scalar field theory. These calculations have been extended in a number of interesting ways in the past few years, e.g., [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76], but we will be particularly interested in [65] where the same techniques were applied to explore the complexity of coherent states in the same QFT.…”
mentioning
confidence: 99%
“…This approach was first applied to a concrete quantum field theory calculation in [57], where the authors adapted Nielsen's approach to evaluate the complexity of the vacuum state of a free scalar field theory. These calculations have been extended in a number of interesting ways in the past few years, e.g., [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76], but we will be particularly interested in [65] where the same techniques were applied to explore the complexity of coherent states in the same QFT.…”
mentioning
confidence: 99%
“…We can see the general behavior of the early-time solutions (18) and (19) and late-time solutions (22) and (23) in the numerical solutions to the equations of motion (16) and (17) in Fig. 1, shown for different choices of the equation of state w (equivalently different values of β).…”
Section: A Expanding Backgroundsmentioning
confidence: 97%
“…Recent studies have also explored different methods of calculating circuit complexity based on the position space wave function or covariance matrix [5][6][7][8][9][10][11], using the geometric technique pioneered by Nielsen [12], and they have extended the idea of complexity to quantum field theory [5,[13][14][15][16][17][18][19][20]. More generally, complexity can serve as one of several diagnostics for determining if a quantum system displays quantum chaos [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the case of single delayed feedback, the quantum dot laser with two delayed feedback proposed in this work will have more rich nonlinear dynamical behaviors by changing the systematical parameter. In reality, the nonlinear dynamics such as periodic and chaotic behaviors that are very significant research subject are also presented and demonstrated based on other interesting physical structures [31][32][33][34][35][36]. Compared with these reported nonlinear dynamical models, the semiconductor quantum dot laser-based periodic and chaotic phenomena will be more useful for the all-optical signal processing in optical communication technology.…”
Section: Introductionmentioning
confidence: 99%